Predictors of knowledge about tuberculosis: results from SANHANES I, a national, cross-sectional household survey in South Africa. (December 2016) - Naidoo, Pamela; Simbayi, Leickness; Labadarios, Demetre; Ntsepe, Yoliswa; Bikitsha, Nwabisa; Khan, Gadija; Sewpaul, Ronel; Moyo, Sizulu; Rehle, Thomas
Abstract Background South Africa is one of the 22 high tuberculosis burden countries that contribute 80 % of the global tuberculosis cases. Tuberculosis is infectious and due to its rapid and easy transmission route poses a threat to population health. Considering the importance of social and psychological factors in influencing health outcomes, appraising knowledge and awareness of tuberculosis, remain vital for effective tuberculosis control. The main aim of this study was to investigate the factors that predict knowledge about tuberculosis among 18–64 year old adults in South Africa. Methods A cross-sectional survey method was used. Multi-stage disproportionate, stratified cluster sampling was used to select households within enumeration areas stratified by province and locality type. Based on the Human Sciences Research Council 2007 master sample, 500 Enumerator Areas representative of the socio-demographic profile of South Africa were identified and a random sample of 20 households was randomly selected from each Enumerator Area, yielding an overall sample of 10 000 households. The tuberculosis module contained in the South African National Health And Nutrition Examination Survey I was the only module that examined the social determinants of an infectious disease. This module was questionnaire-based with no biomarkers obtained to screen for the presence of tuberculosis disease among the participants. Data was collected by administering a researcher developed individual level questionnaire. Simple and multiple linear regression was used to determine the independent variables associated with tuberculosis knowledge. Results Half the sample (52.6 %) was female and the majority of the respondents were black African (76.5 %). More than two thirds (68.0 %) resided in urban areas, 56.9 % did not complete high school and half were not in formal employment. Significant predictors of tuberculosis knowledge were race, sex, completion of high school, being in employment, having a diagnosis of the disease in ones' life-time and learning about tuberculosis from television, brochures, health workers, and teachers. Conclusions To reduce the burden of tuberculosis in South Africa, media campaigns targeting both rural and urban communities should include conveying accurate information about the disease. Policy makers should also address structural barriers that vulnerable communities face.